Multiple endocrine neoplasia type 1 with Zollinger–Ellison syndrome: clinicopathological analysis of a Japanese family with focus on menin immunohistochemistry - Kimura, Noriko; Hirata, Yasuji; Iwashiro, Nozomu; Kijima, Hiroshi; Takayasu, Shinobu; Yamagata, Satoshi; Sakihara, Satoru; Uchino, Shinya; Ohara, Masanori (Frontiers in Endocrinology, 2023)
Background: Multiple endocrine neoplasia type 1 (MEN1) is an autosomal dominant disorder characterized by the occurrence of multiple epithelial neuroendocrine tumors (NETs) and non-NETs in various organs. MEN1 encodes a 610-amino acid-long tumor suppressor protein, menin. The optimal treatment for multiple tumors, identification of the most critical tumors for patient prognosis, and menin immunohistochemistry findings remain controversial. Therefore, we aimed to elucidate these issues through a histological analysis of tumors and tumor-like lesions in a Japanese family, comprising a father and his two sons, who had MEN1 with Zollinger–Ellison syndrome (ZES). Patients and methods: All family members had a germline alteration in exon 10, c.1714-1715 del TC of MEN1, and exhibited multiple synchronous and metachronous tumors. The patients had pulmonary NETs, hyperparathyroidism, hypergastrinemia, pituitary adenomas, pancreaticoduodenal NETs, adrenocortical adenoma with myelolipoma, nodular goiter of the thyroid, lipomas, and angiofibroma. Most tumors were resected and histologically examined. We compared their clinical courses and tumor histology, and conducted menin immunohistochemistry (IHC). Results: Two patients died of pulmonary NET G2. One patient who underwent pancreaticoduodenectomy was cured of ZES; however, the two other patients who did not undergo pancreaticoduodenectomy suffered persistent ZES despite treatment with octreotide. Menin IHC revealed varying NET intensities, ranging from positive to negative stains. Conclusions: Pancreaticoduodenectomy is the most effective treatment for ZES. Long-term follow-up is essential for pulmonary NET G2 owing to the risk of distant metastasis and/or multiplicity. Moreover, the variability of menin IHC in MEN1-related tumors may indicate the pattern of tumor formation rather than the diagnostic utility of menin in MEN1.